Investigation of deltamethrin resistance in salmon lice (Lepeophtheirus salmonis) provides no evidence for roles of mutations in voltage‐gated sodium channels. Issue 2 (17th October 2020) - Tschesche, Claudia; Bekaert, Michaël; Bassett, David I; Mitchell, Chris; North, Ben; Boyd, Sally; Carmona‐Antoñanzas, Greta; Bron, James E; Sturm, Armin
Abstract: BACKGROUND: The pyrethroid deltamethrin is used to treat infestations of farmed salmon by parasitic salmon lice, Lepeophtheirus salmonis (Krøyer). However, the efficacy of deltamethrin for salmon delousing is threatened by resistance development. In terrestrial arthropods, knockdown resistance ( kdr ) mutations of the voltage‐gated sodium channel (Nav ), the molecular target for pyrethroids, can cause deltamethrin resistance. A putative kdr mutation of an L. salmonis sodium channel homologue (LsNav 1.3 I936V) has been identified previously. At the same time, deltamethrin resistance of L. salmonis has been shown to be inherited maternally and to be associated with mitochondrial DNA (mtDNA) mutations. This study assessed potential roles of the above putative kdr mutation as a determinant of deltamethrin resistance in laboratory strains and field populations of L. salmonis . RESULTS: The deltamethrin‐resistant L. salmonis strain IoA‐02 expresses the LsNav 1.3 I936V mutation but was susceptible to the non‐ester pyrethroid etofenprox, a compound against which pyrethroid‐resistant arthropods are usually cross‐resistant if resistance is caused by Nav mutations. In a family derived from a cross between an IoA‐02 male and a drug‐susceptible female lacking the kdr mutation, deltamethrin resistance was not associated with the genotype at the LsNav 1.3 locus ( P  > 0.05). Similarly, in Scottish field populations of L. salmonis, LsNav 1.3 I936V showed no association with deltamethrin resistance. By contrast, genotypes at the mtDNA loci A14013G and A9030G were significantly associated with deltamethrin resistance ( P  < 0.001). CONCLUSION: In the studied L. salmonis isolates, deltamethrin resistance was unrelated to the LsNav 1.3 I936V mutation, but showed close association with mtDNA mutations. Abstract : In Lepeophtheirus salmonis, deltamethrin resistance is not associated with the sodium channel mutation LsNav 1.3 A3041G corresponding to I936V, but is closely linked to mutations in the mitochondrial DNA.